1994
DOI: 10.1091/mbc.5.5.549
|View full text |Cite
|
Sign up to set email alerts
|

TrkA cross-linking mimics neuronal responses to nerve growth factor.

Abstract: TrkA, a tyrosine kinase receptor, is an essential component of the nerve growth factor (NGF) response pathway. The binding of NGF to the receptor induces receptor autophosphorylation and activation of intracellular signaling pathways, resulting in diverse biological effects. We prepared polyclonal antibodies against the entire extracellular domain of rat trkA produced using a baculovirus expression system. These antibodies specifically recognize rat trkA on antigen blots and in immunoprecipitations. Both IgG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
189
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(196 citation statements)
references
References 68 publications
7
189
0
Order By: Relevance
“…For TrkA (763), TrkB (794), and TrkC (798), specific controls were performed on adjacent slides, either by omitting the primary or secondary antibody or by coincubation with either the corresponding homologous control peptide or the heterologous control peptide (Santa Cruz Biotechnology) as previously reported. 38,39 Trk (C-14), TrkA (763), TrkB (794), and TrkC (798) IR were not altered by coincubation with the heterologous peptides and the Trk homologous peptide specifically abolished the signal.…”
Section: Methodsmentioning
confidence: 92%
“…For TrkA (763), TrkB (794), and TrkC (798), specific controls were performed on adjacent slides, either by omitting the primary or secondary antibody or by coincubation with either the corresponding homologous control peptide or the heterologous control peptide (Santa Cruz Biotechnology) as previously reported. 38,39 Trk (C-14), TrkA (763), TrkB (794), and TrkC (798) IR were not altered by coincubation with the heterologous peptides and the Trk homologous peptide specifically abolished the signal.…”
Section: Methodsmentioning
confidence: 92%
“…We predict that small dimeric loop 2 analogues may act as agonists if they can facilitate dimerization of trkB based on observations made in the highly analogous NGF-trkA receptor system. It has been shown that divalent antibodies to trkA can cause the homodimerization of this receptor, leading to signal transduction and NGF-like biological activity in vitro (Clary et al, 1994). It is reassuring that a small peptide mimetic of erythropoietin, produced by a recombinant library technique, possesses full erythropoietin-like biological activity by self-associating to form a dimer that dimerizes the erythropoietin receptor .…”
Section: All Normalized [Arr] Versus Log [A] Curves Whethermentioning
confidence: 99%
“…Then 10 g 1088 (IgG), 10 g anti-rat TrkA (RTA; ref. 72; IgG) or 5 g anti PLC-␥ mixed monoclonal (Upstate Biotechnology, Lake Placid, NY) was added, incubated overnight and recovered with protein-A-or protein-A͞G Sepharose (Pierce). Sepharose beads were washed twice in IP buffer and once with water, then resuspended in 50 l 7 M urea sample buffer (7 M urea͞2% SDS͞125 mM Tris, pH 6.95͞20 mM DTT͞0.1% Bromophenol blue) and heated (55°C for 15-30 min).…”
mentioning
confidence: 99%